Dual roles of calpain in facilitating Coxsackievirus B3 replication and prompting inflammation in acute myocarditis. (15th October 2016) - Li, Minghui; Su, Yangang; Yu, Yong; Yu, Ying; Wang, Xinggang; Zou, Yunzeng; Ge, Junbo; Chen, Ruizhen
Abstract: Background: Viral myocarditis (VMC) treatment has long been lacking of effective methods. Our former studies indicated roles of calpain in VMC pathogenesis. This study aimed at verifying the potential of calpain in Coxsackievirus B3 (CVB3)-induced myocarditis treatment. Methods: A transgenic mouse overexpressing the endogenous calpain inhibitor, calpastatin, was introduced in the study. VMC mouse model was established via intraperitoneal injection of CVB3 in transgenic and wild mouse respectively. Myocardial injury was assayed histologically (HE staining and pathology grading) and serologically (myocardial damage markers of CK-MB and cTnI). CVB3 replication was observed in vivo and in vitro via the capsid protein VP1 detection or virus titration. Inflammation/fibrotic factors of MPO, perforin, IFNγ, IL17, Smad3 and MMP2 were evaluated using western blot or immunohistology stain. Role of calpain in regulating fibroblast migration was studied in scratch assays. Results: Calpastatin overexpression ameliorated myocardial injury induced by CVB3 infection significantly in transgenic mouse indicated by reduced peripheral CK-MB and cTnI levels and improved histology injury. Comparing with CVB3-infected wild type mouse, the transgenic mouse heart tissue carried lower virus load. The inflammation factors of MPO, perforin, IFNγ and IL17 were down-regulated accompanied with fibrotic agents of Smad3 and MMP2 inhibition. And calpain participated in the migration of fibroblasts in vitro, which further proves its role in regulating fibrosis. Conclusion: Calpain plays dual roles of facilitating CVB3 replication and inflammation promotion. Calpain inhibition in CVB3-induced myocarditis showed significant treatment effect. Calpain might be a novel target for VMC treatment in clinical practices. Highlights: Calpain is involved in virus replication in myocarditis. Calpain mediates inflammation infiltration in myocarditis. Calpain might be a candidate for viral myocarditis treatment.